Evaluation of Ayurvedic Shalya Tantra Intervention in the Management of Neonatal Umbilical Granuloma: A Case-Based Observational Study - Rajesh Kapse, Pradnya; Budhwant, Shweta (Journal of Neonatal Surgery, 2024)
Umbilical granuloma is one of the most common neonatal conditions requiring minor surgical intervention. In Ayurvedic surgery (Shalya Tantra), Apamarga Kshara application is mentioned as an effective para-surgical procedure for conditions resembling Nabhi vrana described in classical texts. This observational study aimed to evaluate the efficacy and safety of Apamarga Kshara application in neonates with umbilical granuloma. A total of five neonates aged 7–25 days diagnosed with uncomplicated granuloma were included. The procedure was performed under sterile conditions once daily for three consecutive days. Outcomes were assessed based on reduction in lesion size, complete healing time, and adverse effects. Results showed complete resolution in four cases by Day 5 and one by Day 7, with no infection, bleeding, or recurrence observed during one-month follow-up. The findings suggest that Apamarga Kshara can be a safe, minimally invasive alternative to cauterization for neonatal umbilical granuloma when performed appropriately. Larger randomized controlled trials are recommended.